Anion Coordination Chemistry. - Bowman-James, Kristin, 1946- (John Wiley & Sons, 2012)
Building on the pioneering work in supramolecular chemistry from the last 20 years or so, this monograph addresses new and recent approaches to anion coordination chemistry. Synthesis of receptors, biological receptors and metallareceptors, the energetics of anion binding, molecular structures of anion complexes, sensing devices are presented and computational studies addressed to aid with the understanding of the different driving forces responsible for anion complexation. The reader is promised an actual picture of the state of the art for this exciting and constantly evolving field of supramolecular anion coordination chemistry. The topics range from ion channels to selective sensors, making it attractive to all researchers and PhD students with an interest in supramolecular chemistry.